PENGARUH PERMAINAN PAPAN TEBAK KATA TERHADAP KEMAMPUAN BERBICARA PADA ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 2 KOTA PEKANBARU - Ester Juliana Br Panjaitan; Zulkifli '; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on observation result of pupils speaking ability are not showing optimal devlopment yet, so it is necessary to apply the game board of guess word. This study aims to knowing The influence of game board of guess word against speaking ability children ages 4-5 years in TK Negeri Pembina 2 Kota Pekanbaru. The sample of this study amount to15 pupils. The data collection technique is observation. The data analysis technique is using t-test that use spss 17.0 program. The hypothesis is the game board of guess word usage activity can influencethe speakingability of 4-5 years in TK Negeri Pembina 2 Kota Pekanbaru. It can be know from the result of data analysis obtained thitung=12,093 and sig. (2-tailed)=0.000. because sig. (2-tailed)=0.000<0,05 so, it can be concluded that there is a significant difference of pupils speaking ability after the game board of the guess word usage in learning process. So, it means Hois rejected and Ha is accepted that means there is a very significant difference between before and after doing experiment with apply the game board of the guess word. The influence of game board of guess word against speaking ability children ages 4-5 years in TK negeri pembina 2 Kota Pekanbaru is 58,48%.Keywords: speaking ability, game board of guess word.